Enhancement of trans-cleavage activity of Cas12a with engineered crRNA enables amplified nucleic acid detection - Long T. Nguyen (Nature Portfolio, 2020)
CRISPR-Cas12a based detection systems can be sensitive down to the picomolar range. Here the authors modify the 3′- and 5′-ends of the crRNA and show this enhances trans-cleavage for improved sensitivity.